Using multi-objective optimization to design parameters in electro-discharge machining by wire - Ochoa, Carlos Alberto; Margain, Lourdes Yolanda; Ornelas, Francisco Javier; Jiménez, Sandra Guadalupe; Padilla, Teresa Guadalupe (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2014)
The following paper describes the main objective to follow the methodology used and proposed to obtain the optimal values of WEDM process operation on the machine Robofil 310 by robust parameter design (RPD) of Dr. G. Taguichi [TAGUCHI, G. 1993], through controllable factors which result in more inferences regarding the problem to noise signal (S / N), which for this study is the variability of the hardness of samples from 6061, also studied the behaviour of the output parameters as the material removal rate (MRR) and surface roughness (Ra), subsequently took the RPD orthogonal array and characterized the individuals in the population, each optimal value is a gene and each possible solution is a chromosome, used multi-objective optimization using Non-dominated Sorting Genetic Algorithm to cross and mutate this population to generate better results MRR and Ra.